A Comparative Study to Evaluate the Chronotropic Action of Citalopram, Fluoxetine and Paroxetine on Intact Frog’s Heart (Medical Forum Monthly, 2024)
Objective: To compare the chronotropic action of citalopram, fluoxetine and paroxetine on frog heart.Study Design: Experimental animal studyPlace and Duration of Study: This study was conducted at Yusra Medical and Dental College, Islamabad from October 2015 to February 2016.Materials and Methods: Stunning and pithing of the frog was done following which the heart was exposed. The apex was attached to a force transducer. Heart rate readings were recorded on Power lab. Three groups were designed. In every set of experiments basal readings (without drug) were initially recorded that served as the control and then the tissue was treated with one antidepressant. In Group I we documented the effects of citalopram. In Group II we observed the effects of fluoxetine and in Group III we noted the effect of paroxetine. Statistical analysis was done using SPSS version 22. A p value of less than or equal to 0.05 was considered statistically significant.Results: The isolated heart tissue sample was exposed to 0.5ml of drug. Citalopram at a concentration of 1.54mM reduced the heart rate from 30 to 19 beats/min. Fluoxetine at a concentration 1.6mM brought down the heart rate from 23 to 20 beats/min. Whereas, paroxetine at a concentration of 1.3mM increased the heart rate from 21 to 23 beats/min.Conclusion: Citalopram out of the three chosen drugs caused the most marked reduction n in heart rate. Fluoxetine caused a subtle reduction in heart rate. Paroxetine on the other hand caused a mild increase in heart rate.